Proceeding of 6th International Conference on Advances in Manufacturing and Materials Engineering - Maleque, Md. Abdul (Springer, 2025)
Book presents the proceeding of 6th International Conference on Advances in Manufacturing and Materials Engineering (ICAMME 2024), August 13–14, Kuala Lumpur, Malaysia. It presents articles in topics that outline the state-of-the-art information in manufacturing and materials engineering for academia and industries. The topics represent the strong synergy between manufacturing, materials, design, and management supporting the transition from product service systems to life cycle engineering services as a contributor to high-value manufacturing. The scope of this book also presents a set of new additive manufacturing, 3D printing, and advanced materials with new technology; green technology for United Nations SDGs; modeling and simulation of materials and manufacturing with some classical case examples. It caters to academics and industrial practitioners who have research interests in the latest advances in manufacturing and materials engineering.